Analysis of the Irregularity of Regional Development Based on the Asymmetry of the Empirical Distribution of GRP Per Capita of the Russian Federation Regions - E. R. Valeev; I. A. Kirshin; A. M. Kuznetsova (Статистика и экономика)
Purpose of the study. The implementation of the spatial development strategy of the Russian Federation has led to an increase in scientific and practical interest in the research of interregional differences and the assessment of uneven regional development at all levels of the national economic system. The purpose of this study is to verify the conformity (inconformity) of the empirical distribution of per capita Gross Regional Product (GRP) values of the Russian Federation regions with the normal distribution law to substantiate the specifics of the interregional development of the national economy based on the identification of statistical characteristics of the empirical distribution of GRP per capita.Materials and methods. To achieve this goal, the article developed a methodology for measuring the uneven development of Russian regions by assessing the deviation of the empirical distribution of a sample of per capita GRP data from the normal distribution and determining the degree of asymmetry. The methodological basis was the analytical toolkit of the hypothesis of the normal distribution of the sample set of per capita GRP values for the Russian Federation regions. The article tested the methodology on a statistical sample of data on per capita GRP of the regions of the Russian Federation for 2010-2020; the level of uneven regional development of the economy of the Russian Federation was assessed and the statistical specificity of the revealed uneven development of the regions of the Russian Federation was identified. Identification of statistical outliers in the sample was carried out using the interquartile range method.Results. During the analysis of the sample, statistical outliers were identified. It has been proven that the distribution of per capita GRP of the regions of the Russian Federation is mostly right skewed handed or positively skewed. The observed right-handed orientation of the empirical distribution demonstrated the asymmetry of the distribution of the Russian Federation regions by per capita GRP. The increase in the irregularity of interregional development in the more advanced subjects of the Russian Federation with the per capita GRP index exceeding the average value for the analyzed sample was justified by statistical calculations and the construction of histograms of the empirical distribution of the per capita GRP of the Russian Federation regions.Conclusion. During the analyzed period, the stability of the uneven regional development of the Russian economy is observed. The stability of the positive asymmetry of the empirical distribution means that the basis for the divergence of regional development is the stability of the “club of the majority” of the Russian Federation regions, which form the left tail, and the “club of the minority”, which forms the long right tail of the empirical distribution. The approximation of the Pareto wealth distribution is a good approximation of the profile of the uneven distribution of per capita GRP of the regions of the Russian Federation.